2022
DOI: 10.3390/en15020591
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning to Identify the Potential Marginal Land Suitable for Giant Silvergrass (Miscanthus × giganteus)

Abstract: Developing biomass energy, seen as the most important renewable energy, is becoming a prospective solution in attempting to deal with the world’s sustainability-related challenges, such as climate change, energy crisis, and carbon emission reduction. As one of the most promising second-generation energy crops, giant silvergrass (Miscanthus × giganteus) is highly valued for its high potential for biomass production and low maintenance requirements. Mapping the potential global distribution of marginal land suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In the present study, an ensemble boosted regression tree (BRT) modeling framework that has been used for mapping the environmental suitability of several bioenergy plants 23 27 and medicinal plants 28 , 29 was adopted. This modeling approach allows multicollinearity among covariates and can establish a multivariate empirical relationship between known occurrence points and the suitable environmental conditions in the corresponding locations where the target has been confirmed to have occurred.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, an ensemble boosted regression tree (BRT) modeling framework that has been used for mapping the environmental suitability of several bioenergy plants 23 27 and medicinal plants 28 , 29 was adopted. This modeling approach allows multicollinearity among covariates and can establish a multivariate empirical relationship between known occurrence points and the suitable environmental conditions in the corresponding locations where the target has been confirmed to have occurred.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain the accurate distribution of marginal land suitable for energy plants under current and future climate scenarios, more advanced methods should be employed. The machine learning methods that have proven to be effective in extracting land distribution were applied in this research, combining the occurrence records and growing conditions of energy plants to identify the global marginal land suitable for growing energy plants 22 , 23 . This in-depth analysis of the potential distribution of energy plants under the challenge of climate change proceeds in three steps: (1) choosing cassava, which is one of the most promising energy plants for bioenergy production, as a research object; (2) structuring the dataset with occurrence records and environmental covariates; (3) applying Boosted Regression Trees (BRT), a machine learning method, to evaluate the distribution of potential marginal land suitable for cassava from the perspective of environmental suitability under current and future climate scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The machine learning study results [ 18 ] showed that globally there exist 3068.25 million ha marginal land resources eligible for M. × giganteus cultivation, which are basically located in Africa (902.05 million ha), Asia (620.32 million ha), South America (547.60 million ha) and North America (529.26 million ha). The countries with the largest land resources, Russia and Brazil, hold the first and second places based on the amount of marginal lands suitable for M. × giganteus , with areas of 373.35 and 332.37 million ha, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, LSA has been used in studies associated with a range of different environmental phenomena. For instance, it has been used to map and model urban areas for different particular purposes (Bamrungkhul and Tanaka, 2022; Foroozesh et al, 2022; Hao et al, 2022; Ismaeel and Elsayed, 2022; Saleem et al, 2022) . The driving concept of LSA is to provide decision-makers with the necessary information to evaluate a site suitability for a particular purpose.…”
Section: Introductionmentioning
confidence: 99%